Seven Connected Propositions for Those Who Make Places - Llewellyn Seibold (Oz, 1984)
In the making of places it is often the unstated first thoughts which determine the direction of subsequent architectural considerations and the dominant compositional characteristics. These beginnings can be rich and full of potential or lifeless and myopic..